27‐Hydroxycholesterol Inhibits Sterol Regulatory Element‐Binding Protein 1 Activation and Hepatic Lipid Accumulation in Mice. Issue 4 (24th February 2018) - Li, Di; Long, Weiqing; Huang, Rong; Chen, Ying; Xia, Min
Abstract : Objective: Although 27‐hydroxycholesterol (27‐HC) has been reported as a potent regulator of lipid homeostasis, its role in hepatic lipogenesis remains obscure. The present study was designed to investigate the impact of 27‐HC on sterol regulatory element‐binding protein 1 (SREBP‐1) and hepatic steatosis. Methods: In this study, the 27‐HC level in mice was upregulated by overexpressing CYP27A1 or treating primary hepatocytes with 27‐HC, and then the hepatic lipid accumulation was detected. Results: 27‐HC inhibited hepatic lipid accumulation and decreased the levels of the mature active form of SREBP‐1. The expression of lipogenic genes, including acetyl coenzyme A carboxylase, fatty acid synthase, stearoyl‐coenzyme A desaturase‐1, and glycerol‐3‐phosphate acyltransferase, were also suppressed after 27‐HC intervention. Furthermore, 27‐HC induced expression of insulin‐induced gene‐2 ( Insig‐2 ), an endoplasmic reticulum protein that prevents SREBP activation, both in vivo and in vitro . The inhibitory effect of 27‐HC on SREBP‐1 activation was absent when Insig‐2 was silenced. Finally, coimmunoprecipitation showed that 27‐HC promoted the binding of Insig‐2 to SREBP‐1. Conclusions: These studies demonstrated the suppressive effect of 27‐HC on hepatic lipid accumulation and revealed a novel mechanism by which 27‐HC regulates lipogenesis.